(untitled) (VITAE Academia Biomédica Digital, 2004)
• La gripe aviar («gripe del pollo») y la importancia de su transmisión al ser humano • Avian influenza ("bird flu") and the significance of its transmission to humans • Avian influenza frecuently asked questions • Avian influenza and human health • Human disease from influenza A (H5N1), Thaland, 2004